Experiência do usuário idoso com interfaces de voz - Tubin, Carla (2021)
The use of technologies has contributed to improving the quality of life in the human aging process in several aspects. However, most digital technologies are not designed for the elderly, which makes the user experience (UX) difficult. In smartphones, the low acceptance is related, among other factors, to the physical and cognitive limitations imposed by age, which hinder the interaction of the elderly with these devices. The reported problems are mainly related to low vision and reduced memory capacity and motor problems. For these reasons, voice interfaces are gaining space, since speech is natural for humans and reduces the dependence on graphic interfaces. Therefore, this study aimed to assess whether voice interaction improves the UX of elderly people when intera cting with smartphones. To this end, a controlled experiment was conducted, with 20 elderly people invited, based on the combination of elements of qualitative and quantitative research. Participants who received a list of tasks to be performed with the he lp of a smartphone e. The participants were divided into two groups: where one group performed the tasks first through the interaction by voice and then by touch and the other group followed the opposite order. For the evaluation, questionnaires were applied to categorize the sample, questionnaires to assess participants' expectations, mood, and UX. The results showed that, the main advantages offered by the voice interfaces are related to the reduction of the vision dependency, the practicality, speed , and the easiness related to the motor issues. Some barriers were also found, as among them are problems related to forgetfulness, complications in the elaboration of commands, speech speed, and barriers in the learning of new technologies. Even so, the final results suggest that voice interaction improves the UX of elderly people with smartphones, compared to touch interaction.